Aquatic Life Water Quality Criteria for Selected Pesticides - Tjeerdema, Ronald S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Special Foreword Foreword Preface Aquatic Life Water Quality Criteria Derived via the UC Davis Method I. Organophosphate Insecticides Amanda J. Palumbo, Patti L. TenBrook, Tessa L. Fojut, Isabel R. Faria and Ronald S. Tjeerdema Aquatic Life Water Quality Criteria Derived via the UC Davis Method II. Pyrethroid Insecticides Tessa L. Fojut, Amanda J. Palumbo & Ronald S. Tjeerdema Aquatic Life Water Quality Criteria Derived via the UC Davis Method III. Diuron Tessa L. Fojut, Amanda J. Palumbo & Ronald S. Tjeerdema Index.
Special Foreword -- Foreword -- Preface -- Aquatic Life Water Quality Criteria Derived via the UC Davis Method I. Organophosphate Insecticides -- Aquatic Life Water Quality Criteria Derived via the UC Davis Method II. Pyrethroid Insecticides -- Aquatic Life Water Quality Criteria Derived via the UC Davis Method III. Diuron -- Index.
Keywords: Water pollution; Environmental monitoring; Ecotoxicology; Environmental pollution; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Monitoring/Environmental Analysis; Ecotoxicology; Terrestrial Pollution